2019
DOI: 10.1111/tan.13686
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific criterion to distinguish killer cell immunoglobulin‐like receptor genotypes and haplotypes in a large Eastern Han population

Abstract: With the goal of improving the population‐specific criteria to distinguish KIR genotypes and haplotypes in the region, we examined the KIR gene and haplotype data of Eastern Han based on a large population and analyzed the component genes of centromeric (Cen) and telomeric (Tel) KIR haplotype segments, which may differ in the protection they provide in hematopoietic stem cell transplantation. Samples from 598 families and 2845 unrelated individuals of Eastern Han origin were collected between 2010 and 2017. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…Our results were similar to previously reported data in the region specifically among healthy Lebanese [ 48 , 57 ], Iranian [ 58 , 59 ], and Turkish adults [ 60 ]. Similar results were also reported in Southern Brazil [ 61 , 62 ] and Eastern Han populations in China [ 63 ]. Moreover, the AA genotype profile was the most frequent among our study participants similar to previously reported data in healthy unrelated individuals in Lebanon [ 57 ], Turkey [ 60 ], Iran [ 58 ], and Tunisia [ 64 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar to previously reported data in the region specifically among healthy Lebanese [ 48 , 57 ], Iranian [ 58 , 59 ], and Turkish adults [ 60 ]. Similar results were also reported in Southern Brazil [ 61 , 62 ] and Eastern Han populations in China [ 63 ]. Moreover, the AA genotype profile was the most frequent among our study participants similar to previously reported data in healthy unrelated individuals in Lebanon [ 57 ], Turkey [ 60 ], Iran [ 58 ], and Tunisia [ 64 ].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the SSOP method, LABType ® SSO Kits (One Lambda) and the Luminex 200 system were used. The criteria for KIR genotype assignments have been described in a previous report [24].…”
Section: Hla and Kir Typingmentioning
confidence: 99%